RESPONDING TO THE CALLS TO ACTION: REFLECTIONS ON TEACHING MANDATORY INDIGENOUS EDUCATION TO TEACHER CANDIDATES IN ONTARIO - Watson, Kaitlyn; Currie-Paterson, Natalie (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2018)
Drawing on reflexive conversations, we describe our experiences teaching a new mandatory course in Indigenous education at Western University in London, Ontario. By discussing the successes, challenges, and mistakes made while teaching this course, we hope to continue to decolonize our practice as settlers, PhD students, and educators with the goal of working towards reconciliation in education and society.